Long-term results of fallot tetralogy total correction with the use of combined pulmonary valve biological prostheses (case report) - Zinkovskyi, M. F.; Goryachev, A. G.; KravchenkoV. І.; DykuhaS. О.; Atamanyuk, M. Yu.; KarimovО.; Hrapunov, V. N.; Babadzanov, K. B. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Long-term survival with good clinical and hemodynamic results is shown on the example of 3 cases of Fallot tetralogy total correction with the use of personally made xenoaortic bioprostheses in the pulmonary artery position (terms of observation: 38, 37, 20 years).